Implementation of Think Pair Share Learning Model to Improve Cognitive Learning Outcomes on the Immune System Topic in MA Ma’arif Ambulu - Kharisma Shofiudin Ma’sum Alwi; Imam Bukhori; Miftahul Hakim (Journal of Insan Mulia Education, 2025)
In reality, biology learning processes in schools still employ conventional methods, where the teacher is the center of learning and students tend to be passive. Based on observations and interviews with biology teachers at MA Ma'arif Ambulu, it was revealed that the lack of student activeness and concentration has resulted in low student scores that have not met the Minimum Mastery Criteria (MMC). Therefore, this study aims to improve students' cognitive learning outcomes on human immune system material by applying the Think Pair Share (TPS) learning model in class XI IPA 1 MA Ma'arif Ambulu. The TPS learning model is a cooperative learning approach that involves three main steps: Think, Pair, and Share. This study was conducted using the Classroom Action Research (CAR) method in class XI IPA 1 MA Ma'arif Ambulu, involving 21 students. The study focused on human immune system material and consisted of two cycles, with each cycle comprising two meetings. Data were collected through interviews, observations, and tests, and then analyzed using quantitative data analysis methods. The results showed an increase in student learning outcomes, from a classical average of 38% in the pre-cycle to 71% in the second cycle, meeting the minimum mastery target. Thus, TPS is effective in improving students' cognitive learning outcomes on human immune system material.